Remote epitaxy of InxGa1-xAs (0 0 1) on graphene covered GaAs(0 0 1) substrates - Henksmeier, T.; Schulz, J.F.; Kluth, E.; Feneberg, M.; Goldhahn, R.; Sanchez, A.M.; Voigt, M.; Grundmeier, Guido; Reuter, Dirk (Journal of Crystal Growth)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Low Areal Densities of InAs Quantum Dots on GaAs(100) Prepared by Molecular Beam Epitaxy - Verma, A.K.; Bopp, F.; Finley, J.J.; Jonas, B.; Zrenner, A.; Reuter, Dirk (Journal of Crystal Growth)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Optical in-situ temperature management for high-quality ZnO molecular beam epitaxy - Albert, M.; Golla, C.; Meier, Cedrik (Journal of Crystal Growth)

InAs heteroepitaxy on nanopillar-patterned GaAs (111)A - Kunnathully, Vinay S.; Riedl, Thomas; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg K.N. (Journal of Crystal Growth)

InAs heteroepitaxy on nanopillar-patterned GaAs (111)A - Kunnathully, Vinay S.; Riedl, Thomas; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg (Journal of Crystal Growth)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Molecular beam epitaxy growth and temperature-dependent electrical characterization of carbon-doped GaAs on GaAs(1 1 1)B - Henksmeier, Tobias; Shvarkov, Stepan; Trapp, Alexander; Reuter, Dirk (Journal of Crystal Growth)

Linear and nonlinear behaviour of near-IR intersubband transitions of cubic GaN/AlN multi quantum well structures - Wecker, T.; Jostmeier, T.; Rieger, T.; Neumann, E.; Pawlis, A.; Betz, M.; Reuter, Dirk; As, Donat Josef (Journal of Crystal Growth)

Overcoming Ehrlich-Schwöbel barrier in (1 1 1)A GaAs molecular beam epitaxy - Ritzmann, Julian; Schott, Rüdiger; Gross, Katherine; Reuter, Dirk; Ludwig, Arne; Wieck, Andreas D. (Journal of Crystal Growth)

Focused ion beam supported growth of monocrystalline wurtzite InAs nanowires grown by molecular beam epitaxy - Scholz, Sven; Schott, Rüdiger; Labud, Patrick A.; Somsen, Christoph; Reuter, Dirk; Ludwig, Arne; Wieck, Andreas D. (Journal of Crystal Growth)

A modified gradient approach for the growth of low-density InAs quantum dot molecules by molecular beam epitaxy - Sharma, Nandlal; Reuter, Dirk (Journal of Crystal Growth)

Cubic GaN quantum dots embedded in zinc-blende AlN microdisks - Bürger, M.; Kemper, R.M.; Bader, C.A.; Ruth, M.; Declair, S.; Meier, Cedrik; Förstner, Jens; As, D.J. (Journal of Crystal Growth)
Microresonators containing quantum dots find application in devices like single photon emitters for quantum information technology as well as low threshold laser devices. We demonstrate the fabrication of 60 nm thin zinc-blende AlN microdisks including cubic GaN quantum dots using dry chemical etching techniques. Scanning electron microscopy analysis reveals the morphology with smooth surfaces of the microdisks. Micro-photoluminescence measurements exhibit optically active quantum dots. Furthermore this is the first report of resonator modes in the emission spectrum of a cubic AlN microdisk.
Keywords: tet_topic_qd; tet_topic_microdisk

Growth of cubic GaN on 3C–SiC/Si (001) nanostructures - Kemper, R.M.; Hiller, L.; Stauden, T.; Pezoldt, J.; Duschik, K.; Niendorf, T.; Maier, H.J.; Meertens, D.; Tillmann, K.; As, D.J.; Lindner, Jörg (Journal of Crystal Growth)
We report on the molecular beam epitaxy growth of cubic GaN on 3C–SiC (001) nanostructures. Transmission electron microscopy (TEM) studies show phase-pure cubic GaN crystals with a low defect density on top of the post shaped 3C–SiC nanostructures and GaN grown on their sidewalls, which is dominated by {111} planar defects. The nanostructures, aligned parallel and perpendicular to the [110] directions of the substrate, are located in anti-phase domains of the 3C–SiC/Si (001) substrate. These anti-phase domains strongly influence the optimum growth of GaN layers in these regions. TEM measurements demonstrate a different stacking fault density in the cubic GaN epilayer in these areas.

(100) GaAs/AlxGa1−xAs heterostructures for Zeeman spin splitting studies of hole quantum wires - Trunov, K.; Reuter, Dirk; Ludwig, A.; Chen, J.C.H.; Klochan, O.; Micolich, A.P.; Hamilton, A.R.; Wieck, A.D. (Journal of Crystal Growth)

Growth of cubic GaN on nano-patterned 3C-SiC/Si (001) substrates - Kemper, R.M.; Weinl, M.; Mietze, C.; Häberlen, M.; Schupp, T.; Tschumak, E.; Lindner, Jörg; Lischka, K.; As, Donald (Journal of Crystal Growth)
Non-polar relaxed cubic GaN was grown by molecular beam epitaxy (MBE) on nano-patterned 3C-SiC/Si (0 0 1)substrates with negligible hexagonal content and less defect density than in planar cubic GaN layers.Nano-patterning of 3C-SiC/Si(001) is achieved by self-ordered colloidal masks for the first time. The method presented here offers the possibility to create nano-patterned cubic GaN without the need for a GaN etching process andt hus isa potential alternative to the conventional top–down fabrication techniques.

The effects of annealing on non-polar (112¯0) a-plane GaN films - Hao, Rui; Zhu, T.; Häberlen, M.; Chang, T.Y.; Kappers, M.J.; Oliver, R.A.; Humphreys, C.J.; Moram, M.A. (Journal of Crystal Growth)
Non-polar a -plane (1 1 2 ̄ 0) GaN films were grown on r-plane sapphire by metal–organic vapor phase epitaxy and were subsequently annealed for 90 min at 1070°C. Most dislocations were partial dislocations, which terminated basal plane stacking faults. Prior to annealing, these dislocations were randomly distributed. After annealing, these dislocations moved into arrays oriented along the [0 0 0 1] direction and aligned perpendicular to the film–substrate interface throughout their length, although the total dislocation density remained unchanged. These changes were accompanied by broadening of the symmetric X-ray diffraction 1 1 2 ̄ 0 w-scan widths. The mechanism of movement was identified as dislocation glide, occurring due to highly anisotropic stresses (confirmed by X-ray diffraction lattice parameter measurements) and evidenced by macroscopic slip bands observed on the sample surface. There was also an increase in the density of unintentionally n-type doped electrically conductive inclined features present at the film–substrate interface (as observed in cross-section using scanning capacitance microscopy), suggesting out-diffusion of impurities from the substrate along with prismatic stacking faults. These data suggest that annealing processes performed close to film growth temperatures can affect both the microstructure and the electrical properties of non-polar GaN films.

Understanding the cubic AlN growth plane from first principles - Rauls, E.; Wiebe, J.; Schmidt, Wolf Gero (Journal of Crystal Growth)

Structural characterization of cubic and hexagonal GaN thin films grown by IBA–MBE on SiC/Si - Häberlen, M.; Gerlach, J.W.; Murphy, B.; Lindner, Jörg; Stritzker, B. (Journal of Crystal Growth)
Buried ion beam synthesized 3C-SiC layers were revealed to the surface of silicon wafers to provide lattice matched substrates for GaN thin film epitaxy. Both epitaxial SiC/Si(1 1 1) and SiC/Si(0 0 1) growth surfaces with either six- or four-fold crystal symmetry, respectively, were formed. GaN thin film growth was achieved by ion beam assisted molecular beam epitaxy (IBA–MBE) which – owing to the energy and momentum transfer of the ions – allows to deposit epitaxial thin films at particularly low growth temperatures where both the stable hexagonal and the metastable cubic polytype of GaN can be formed. It is shown by X-ray diffraction (XRD) and cross-sectional transmission electron microscopy (XTEM) that using appropriate fluxes of Ga atoms both purely hexagonal and purely cubic GaN films can be grown epitaxially on SiC/Si(1 1 1) and SiC/Si(0 0 1), respectively. Thereby Ga rich growth conditions seem to stabilize the formation of the cubic polytype. It is obvious from XTEM studies that the high density of crystal defects in the SiC layer is not transferred onto the growing GaN films and that the crystalline quality of GaN films improves with increasing film thickness. The influence of surface roughness and wettability, interfacial cavities and the nucleation of twin-type defects at the GaN/SiC interface on the crystalline quality of the GaN thin films is discussed.

Growth and characterisation of GaAs/InGaAs/GaAs nanowhiskers on (111) GaAs - Regolin, I.; Sudfeld, D.; Lüttjohann, S.; Khorenko, V.; Prost, W.; Kästner, J.; Dumpich, G.; Meier, Cedrik; Lorke, A.; Tegude, F.-J. (Journal of Crystal Growth)

Sticking behavior of the dopants Si, C, and Be upon re-evaporation of individually doped GaAs(100) - Yang, J.L.; Reuter, Dirk; Wieck, A.D. (Journal of Crystal Growth)